RESEARCH ON THE INCENTIVE EFFECT OF ADDITIONAL DEDUCTION FOR R&D EXPENSES ON CAPITAL: A REVIEW - Wu Shuangshuang; Mohd Nor Hakimin Yusoff (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2024)
In recent years, in order to promote the improvement of the Chinese overall strength in scientific and technological innovation, the Chinese government has implemented preferential tax policies for scientific and technological enterprises to deduct R&D expense, to reduce the tax burden, to reduce costs and expenses, to increase enterprise cash flow, and to encourage enterprises to increase investment in R&D expense. The article is based on the theory of tax regulation, to review the Chinese government’s preferential tax policy of additional deduction for R&D expenses in scientific and technological enterprises. With different empirical models, this article is made an empirical analysis and research on the incentive effect of additional deduction for R&D expenses on the capital investment of scientific and technological enterprises from multiple perspectives. A comprehensive demonstration of the positive incentive effect of preferential tax policies is of great significance for the Chinese government to regulate scientific and technological investment, to enhance the competitive advantage of science and technology by tax policies, to realize science and technology self-reliance.